(untitled) (Journal of Comparative & International Higher Education, 2024)
The Russia-Ukraine war has significantly impacted the outbound student mobility of Russian students, exacerbating an already troubled system recovering from the COVID-19 pandemic-related travel restrictions and grappling with the deteriorating currency exchange rates after the annexation of Crimea. This paper highlights and explains the positive role virtual student mobility can play in shaping and supporting the international education aspirations of Russian students amidst these entangled crises. The research draws upon the Aspirations-Capabilities framework, the notion of mobility capital as a migratory resource, and different states of (im)mobility to shed light on the affordance of virtual mobility formats to help Russian students escape the state of acquiescent immobility. Using an interpretive phenomenological approach, the study analyzes 16 semi-structured in-depth interviews conducted with Russian students who participated in various forms of virtual mobility between 2020 and 2023. The findings reveal that virtual mobility offers a unique opportunity to bolster Russian students’ capacity to aspire to international studies despite mobility suppressing climate through acting as a “rite of passage” en route to international education, increasing language confidence, and challenging negative portrayals of hostility towards Russian students in the West. The richness of virtual mobility experience in terms of communication with teachers and students from abroad plays a key role in activating this affordance.